Effects of food availability and irradiance on photosynthesis and reproductive investment in sea slugs Elysia viridis - Ribeiro, Mariana Isabel Teixeira (2018)
This work aims to investigate the role of food and light availability in the photosynthesis and maternal investment of the sea slug Elysia viridis. Two experiments were conducted to test the importance of food – Codium tomentosum – and to test the importance of the autotrophic component with three different food and light regimes, respectively. The results suggest that maternal investment is greater when food exists in abundance and less when animals are starving. A positive relationship was also observed between the abundance of food and the length of the animal, the egg mass area and egg volume. The study investigating the maternal investment in three different light regimes had some experimental limitations; however, it was observed that sea slugs exposed to an average light intensity had a greater investment in reproduction. It can be concluded that both heterotrophic and autotrophic components influence the investment of these sea slugs in their reproduction.